EPIDEMIOLOGY OF PATHOGENIC MICROORGANISMS (International journal of medical sciences, 2025)
This scientific work provides an in-depth analysis of the epidemiological characteristics of pathogenic microorganisms and highlights the main factors affecting their spread among the population. The study scientifically assesses the biological characteristics of pathogens, their ecological adaptation, sources of infection, reservoirs and transmission mechanisms. It also systematically studies the formation of diseases, the determinants of their epidemic process, the level of virulence of the pathogen and the role of carrier organisms. The work also describes modern epidemiological monitoring methods, the scientific basis for the detection, forecasting and control of infections.